2018
DOI: 10.1038/s41434-018-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

Nanosphere-mediated co-delivery of VEGF-A and PDGF-B genes for accelerating diabetic foot ulcers healing in rats

Abstract: Diabetic ischemic ulcer is an intractable diabetic complication. Angiogenesis is a critical factor for wound healing in patients with diabetic foot wounds. Sustained gene delivery could be notably necessary in modulating gene expression in chronic ulcer healing and might be a promising approach for diabetic foot ulcers. In the present study, Sprague-Dawley rats were used to establish diabetic foot ulcer models by streptozotocin and skin biopsy punch. The plasmids expressing VEGF-A and PDGF-B were prepared and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 32 publications
2
34
0
1
Order By: Relevance
“…Gene therapy for the delivery of growth factors is also in an era of emerging treatment options for wound healing [151]. Shi et al reported a combined gene transfer of VEGF-A and PDGF-B for diabetic foot ulcers in rats [152]. The aim of the study was to analyze whether the engineered growth factors based plasmid-loaded nanospheres could be upregulated in streptozotocin-induced diabetic rats and improve the wound healing.…”
Section: Reviewmentioning
confidence: 99%
“…Gene therapy for the delivery of growth factors is also in an era of emerging treatment options for wound healing [151]. Shi et al reported a combined gene transfer of VEGF-A and PDGF-B for diabetic foot ulcers in rats [152]. The aim of the study was to analyze whether the engineered growth factors based plasmid-loaded nanospheres could be upregulated in streptozotocin-induced diabetic rats and improve the wound healing.…”
Section: Reviewmentioning
confidence: 99%
“…The rats were allowed to develop diabetes for 4 weeks. 18 At 3, 6 or 8 weeks after feeding and 4 weeks after STZ injection, the body weight was recorded for all the rats.…”
Section: Induction Of Diabetesmentioning
confidence: 99%
“…After randomization, the animals were anesthetized with thiopental sodium (50 mg/kg) and a full thickness foot ulcer was made on dorsal hind foot by using Westcott scissor and 6 mm punch biopsy. 18…”
Section: Creation Of Diabetic Foot Ulcermentioning
confidence: 99%
“…1 Diabetic foot ulceration (DFU), a severe complication of DM, could dramatically influence the life quality of patients and could even be life-threatening. 2 Chronic wounds induced by diabetic foot are physiological impairments characterized by deferments in healing, which will lead to severe morbidity and mortality. 3 More than 80% of foot ulcers may end up with lower extremity diabetic amputations, thus promoting the wound healing of ulcers and preventing recurrence of ulceration becoming a major focus in preventing amputation.…”
Section: Introductionmentioning
confidence: 99%